Pola Asuh Ayah Dalam Meningkatkan Perilaku Prososial Anak Usia Dini - Shari, Destita; Rihlah, Jauharotur; Munawaroh, Risalatul; Asmaiyah, Nur (UKInstitute, 2024)
The parenting seminar aims to enhance fathers' understanding of parenting styles to improve prosocial behavior and encourage better collaboration between fathers and mothers in early childhood parenting. The background of this community service implementation is the low knowledge of fathers regarding various parenting concepts and their impact on all aspects of child development. This community service activity took place in RT 009, Taman Pondok Legi Housing, Pepelegi Waru Sidoarjo, with the target participants being 20 married couples who are residents of RW 009. The community service was carried out using a seminar method, which included QA sessions and mentoring for married couples to apply the appropriate parenting styles. The activities began with coordination and preparation with the partners, material development, seminar implementation, mentoring, and evaluation. The seminar was attended by 20 married couples, totaling 40 participants.The results of the seminar, based on pre-test and post-test evaluations, showed the following improvements: in terms of knowledge enhancement, the average score for questions about parenting styles increased from 3.2 to 4.8; in terms of involvement enhancement, the average score for involvement in parenting increased from 2.5 to 4.2; in terms of understanding the father's role, the average score for understanding the father's role in parenting increased from 3.0 to 4.7; and in terms of enhancing prosocial behavior, the average score for teaching prosocial behavior increased from 2.8 to 4.5. The evaluation was conducted through pre-test and post-test, showing increased participants' understanding. The conclusion of this community service is that it can significantly contribute to increasing fathers' awareness and ability to nurture early childhood children. The suggestion from this community service is that with an interactive seminar approach and continuous mentoring, the role of fathers in parenting can be more optimal, allowing children to develop prosocial behavior that is appropriate and in line with contemporary developments.Abstrak. Seminar parenting ini bertujuan untuk meningkatkan pemahaman ayah tentang pola asuh dalam meningkatkan perilaku prososial dan juga mendorong kolaborasi yang lebih baik antara ayah dan ibu dalam pengasuhan anak usia dini. Latar belakang dari pelaksanaan pengabdian masyarakat ini adalah oleh rendahnya pengetahuan ayah mengenai konsep pola asuh yang beragam dan pengaruhnya terhadap seluruh aspek perkembangan anak. Pelaksanaan pengabdian masyarakat ini bertempat di RT 009 Perumahan Taman Pondok Legi, Pepelegi Waru Sidoarjo. Dengan sasaran peserta adalah 20 pasangan suami istri warga RW 009. Pengabdian ini dilaksanakan dengan metode seminar dan mencakup sesi tanya jawab dan pendampingan pasangan suami istri untuk mengaplikasikan pola asuh yang sesuai. Dimulai dari kegiatan koordinasi persiapan dengan mitra, pengembangan materi, pelaksanaan seminar, pendampingan dan evauasi. Seminar ini dihadiri oleh 20 pasangan suami istri sehingga total peserta 40 orang. Hasil dari seminar ini pada saat pre test dan post test dalam hal peningkatan pengetahuan skor rata-rata pertanyaan tentang jenis pola asuh meningkat dari 3.2 menjadi 4.8, dalam hal peningkatan keterlibatan skor rata-rata untuk keterlibatan dalam pengasuhan meningkat dari 2.5 menjadi 4.2., lalu dalam hal peningkatan pemahaman peran ayah skor rata-rata untuk pemahaman tentang peran ayah dalam pengasuhan meningkat dari 3.0 menjadi 4.7, kemudian dalam hal peningkatan perilaku prososisal skor rata-rata untuk mengajarkan perilaku prososial meningkat dari 2.8 menjadi 4.5 Evaluasi dilakukan melalui pre-test dan post-test yang menunjukkan peningkatan pemahaman peserta. Kesimpulan dari Pengabdian ini dapat memberikan kontribusi yang signifikan dalam meningkatkan kesadaran dan kemampuan ayah dalam mengasuh anak usia dini. Saran dalam pengabdian ini adalah dengan pendekatan seminar yang interaktif dan pendampingan yang berkelanjutan, diharapkan peran ayah dalam pengasuhan dapat lebih optimal, sehingga anak-anak dapat berkembang dengan perilaku prososial yang baik dan sesuai dengan perkembangan zaman.